In between human–animal bodies: transcorporeal experiences in hittite anatolia - Della Casa, Romina (2024)
Fil: Della Casa, Romina. Pontificia Universidad Católica Argentina. Facultad de Ciencias Sociales. Departamento de Historia; Argentina